2001
DOI: 10.1074/jbc.m006992200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants of Voltage-dependent Gating and Binding of Pore-blocking Drugs in Transmembrane Segment IIIS6 of the Na+ Channel α Subunit

Abstract: Mutations of amino acid residues in the inner twothirds of the S6 segment in domain III of the rat brain type IIA Na ؉ channel (G1460A to I1473A) caused periodic positive and negative shifts in the voltage dependence of activation, consistent with an ␣-helix having one face on which mutations to alanine oppose activation. Mutations in the outer one-third of the IIIS6 segment all favored activation. Mutations in the inner half of IIIS6 had strong effects on the voltage dependence of inactivation from closed sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
203
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(219 citation statements)
references
References 42 publications
15
203
1
Order By: Relevance
“…[47][48][49][50] The different clinical actions of the drugs can be explained in terms of specific effects on channel function. AEDs that modulate voltage-dependent Na ϩ channels produce a voltage-and use-dependent block of the channels by binding predominantly to the inactivated state of the channels, thus suppressing high-frequency, repetitive action potential firing.…”
Section: Voltage-gated Sodium Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…[47][48][49][50] The different clinical actions of the drugs can be explained in terms of specific effects on channel function. AEDs that modulate voltage-dependent Na ϩ channels produce a voltage-and use-dependent block of the channels by binding predominantly to the inactivated state of the channels, thus suppressing high-frequency, repetitive action potential firing.…”
Section: Voltage-gated Sodium Channelsmentioning
confidence: 99%
“…The binding of phenytoin and the frequencydependent block of Na ϩ current was diminished by mutations F1764A and Y1771A in transmembrane segment IVS6. 47,48 Further studies with lamotrigine and some related compounds revealed that the nearby I1760 and additional residues in IIIS6 are also critical to drug binding 49,50,61 (FIG. 1).…”
Section: Voltage-gated Sodium Channelsmentioning
confidence: 99%
“…, where h is the fraction of inactivated channels in control, and I D is the fraction of channels blocked at the drug concentration [D] (Kuo and Bean, 1994;Yarov-Yarovoy et al, 2001). The holding potential of −90 mV was used for BgNa v 1-4, and −60 mV for both BgNa v 1-1 and BgNa v 1-4 E1689K channels.…”
Section: K1689e Is Responsible For the Differences In Voltage-dependementioning
confidence: 99%
“…In addition, more recently, some residues arising from DIII-S6 and DI-S6 have also been shown to be the local anaesthetic binding sites. Yarov-Yarovoy et al (2001) showed that mutations L1465A, N1466A, and I1469A in the segment DIII-S6 of the rat brain type IIA sodium channel decreased the affinity of the inactivated sodium channels for etidocaine. Lysine mutations of rat skeletal muscle m1 sodium channel S1276 and L1280 (homologous to L1465 in the rat brain type IIA channel) in the segment DIII-S6 reduced the inactivated state affinity for bupivacaine (Wang et al, 2000).…”
Section: Hirose Et Al Kifmk Suppresses Insulin Signalling 225mentioning
confidence: 99%
“…No residues in IR structure are elucidated as important determinants for binding lignocaine. In sodium channels, some residues of the segments 6 of domains IV (DIV-S6), III (DIII-S6), and I (DI-S6), but not of domain II (DII-S6), are considered to be forming local anaesthetic binding sites (Ragsdale et al, 1994;Nau et al, 1999;Wang et al, 2000;Yarov-Yarovoy et al, 2001). Kuroda et al (1996; studied the interactions between local anaesthetics and sodium channel inactivation gaterelated peptides (G1484 -K1495; Figure 1), which are dissected from the III -IV linker connecting DIII-S6 and DIV-S1 of rat brain type IIA sodium channel.…”
Section: Introductionmentioning
confidence: 99%